Optimised combinatorial control strategy for active anti-roll bar system for ground vehicle - Zulkarnain, N.; Zamzuri, H.; Saruchi, S. A.; Hussain, A.; Mokri, S. S.; Jedi, A.; Razali, N.; Mohd Nordin, I. N. A. (Science Publishing Corporation, 2018)
The objective of this paper is to optimise the proposed control strategy for an active anti-roll bar system using non-dominated sorting genetic algorithm (NSGA-II) tuning method. By using an active anti-roll control strategy, the controller can adapt to current road conditions and manoeuvres unlike a passive anti-roll bar. The optimisation solution offers a rather noticeable improvement results compared to the manually-tuned method. From the application point of view, both tuning process can be used. However, using optimisation method gives a multiple choice of solutions and provides the optimal parameters compared to manual tuning method.